Examination of Performance Management Targets in Case of an International Corporation’s Eastern Hungarian Operating Unit - Nemeth, Zoltan; Dajnoki, Krisztina; Suto, David; Fenyves, Veronika (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
Nowadays, due to the social and economic changes, the human is already the main resource which determines the successfulness of corporations. The expertise in managing the human resources is a key factor of competitiveness therefore it has become a strategic question. Primary aim of the treatise is to outline the most important principles, targets and peculiarities of performance management system, which is a central element of human resource management, as well as its interconnectedness with the individual performance evaluation and human resource development through the mirror of one of today’s biggest Hungarian economic corporations. We aimed to explore, by means of document analysis as well as methods of case study and interview, how the targets of performance management are used for increasing the economic productivity, preserving the competitiveness, retaining and enhancing the satisfaction of workers. It can be stated that the PM system was continuously improved in case of the organization examined because the corporate goals and the expected performances were adjusted to the changing market demands over time but, at the same time the goal of differentiation has remained unchanged. Each worker evaluates his/her performance individually, the base of which is the extent of contribution to the corporate results. Based on the results, it can overall be stated that such a well-functioning performance management system is applied in the operating unit of the corporation examined which is strongly supported by the organizational culture and which contributes to the joint fulfilment of personal as well as organizational goals.